Aboveground biomass and carbon stock estimation in logged-over tropical lowland forest - Abdul Majid, Nur Kyariatul Syafinie (2012)
Global climate change is one of the most pressing environmental concerns of humanity. This is cause by the increasing concentration of greenhouse gases (GHG) especially carbon dioxide (CO2). Forest plays a vital role in controlling the capacity of atmosphere CO2 where they are also known as a ‘carbon sinker’ as they manage to significantly capture carbon and store them as biomass. Tropical forest ecosystem is believed to sequester a large number of carbon (C) compared to other natural ecosystem where the majority of C stored in the aboveground vegetation. In Malaysia, accurate information on aboveground carbon storage is lacking. Hence,the objectives of this study were to estimate and develop equations of biomass in logged-over tropical lowland forest, measure wood density of selected trees in the study area and to quantify carbon in different type of aboveground biomass components. This study was conducted at two logged-over tropical lowland forest; Bubu Forest Reserve, Perak Darul Ridzuan and Ayer Hitam Forest Reserve,Selangor Darul Ehsan. In both study sites, ten 50m x 20m plots were randomly established within the study area and trees with 10cm DBH (diameter breast height) were inventoried. Sub-sampling of seedlings (1m x 1m) and saplings (3m x3m) were also carried out within the 50m x 20m plot. Forest litter were sampled using 22 one meter square quadrate in 50m x 20m plot. Sub-sampling of downed woody material was also done within the plot. Their length, diameter and height were recorded. Decayed downed woody material were categorised according to three states of decomposition. Samples were taken, dried; weight and density were calculated as dry mass divided by fresh volume. In Bubu Forest Reserve, 14 trees were selected and felled and biomass of each component was weighed separately (main stem, branches, twigs, leaves) and discs from three sections (base, middle, top) of the main stem were obtained for further testing. After being weighted at the site, all samples were brought to the laboratory for further analysis. Samples were analysed using CNS 2000 Elemental Analyser for C content. From the analysis,two allometric equations was formulate for two different group based on the wood density from tree sampled which is high wood density class (AGB = 0.05633DBH 2.75756) and medium wood density class (AGB = 0.00023DBH 3.75745). From this information, it was determined that the Bubu Forest Reserve aboveground biomass was 501.30 t ha-1 while Ayer Hitam Forest Reserve aboveground biomass was 420.08 t ha-1. The result also showed that tree component stored 98% of the aboveground biomass, followed by downed woody (0.96%), forest litter 0.76%)and palm (0.28%). The carbon content for all biomass components ranged from 45% to 47%. From these results, the carbon stock for Bubu Forest Reserve was estimated to be 225 t C ha-1 while for Ayer Hitam Forest Reserve, it was 189.18 t C ha-1. The biomass equation develops for this study can be used to assess aboveground biomass in the forest specially in areas where tree cutting is not allowed. However, additional ground based data are needed to increase the precision of forest biomass estimate.